Learning analytics for enhanced professional capital development: a systematic review - de La Hoz-Ruiz, Javier; Khalil, Mohammad; Domingo Segovia, Jesús; Liu, Qinyi (Frontiers in Psychology, 2024)
Background/Motivation This article presents a systematic review aimed at examining the utilization of learning analytics (LA) to enhance teachers’ professional capital. Aim The study focuses on three primary research questions: (1) exploring the characteristics and approaches of LA in professional capital, (2) investigating suggestions from LA for assessing and improving professional capital, and (3) examining variables studied in enhancing the most intricate dimension of professional capital using LA. Methodology To address the research objectives, a systematic review was conducted focusing on the key concepts “learning analytics” and “professional capital.” Following the procedures outlined encompassed in four stages: identification, screening, inclusion, and adequacy. The PRISMA 2009 protocol guided the systematic review process. Principal findings The findings of the study underscore the efficacy of LA as a catalyst for improving professional capital, particularly through collaborative learning and the utilization of tools like forums and online learning platforms. Social capital emerges as a pivotal component in integrating diverse types of professional capital, fostering opportunities for knowledge creation and social networking. Conclusion/Significance In conclusion, the study highlights the paramount significance of addressing teachers’ professional capital development through collaborative approaches and leveraging technology, particularly in primary education. The article concludes by emphasizing the imperative for more research and knowledge dissemination in this field, aiming to ensure equity in learning and address the challenges posed by the COVID−19 pandemic.